Role Of Village Owned Enterprises (Bumdes) In Community Empowerment Country House Of Three District Ambon Bay - Elisya Sopaheluwakan; Leonard Kakisina; Raihana Kaplale (Cita konsultindo, 2023)
This research is a qualitative research that aims to understand the phenomena experienced by research subjects in the field using observation, interview and documentation techniques. The results of this study indicate that BUMDes Tuniwaya in empowering the people of Negeri Rumah Tiga has four business units, namely savings and loan business units, agricultural shops, rental of tents, chairs and goods transportation services. In empowering the community's economy, quite effective results are obtained from the savings and loan business unit because the community can build and develop their businesses so that they can create jobs for others. Based on UNICEF's theory of the success of community empowerment through 5 dimensions, then the results of the research that has been conducted state that BUMDes Tuniwaya has not properly implemented the dimensions of participation and control dimensions .